THE CORRELATION BETWEEN STUDENTS’ SELF-EFFICACY AND THEIR LISTENING COMPREHENSION - Anggun Bakti; Dedi Sofyan; Elfrida . (Journal of English Education and Teaching, 2019)
The aim of this research was to find out the correlation of students’ listening self-efficacy and their listening comprehension.. The population of this research was the Eighth Semester English Education Study Program Students of Universitas Bengkulu in the 2018/2019. The sample was taken by using total sampling of the students who has TOEFL score below 450.  There were 40 students as the sample from two classes. There were two research instruments used in this research, listening test and self-efficacy questionnaire. Based on the data analysis, it was found that the r-obtained was 0.20. It means that there is a correlation between the students’ self-efficacy and their listening comprehension.  As a consequence, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Since the r- obtained (0.20) was lower than the r-table(0.3125), the correlation was not really significant.